HUBUNGAN ANTARA FAKTOR INDIVIDU, BEBAN KERJA DAN SHIFT KERJA DENGAN KELELAHAN KERJA PADA PERAWAT DI RSJD Dr. AMINO GONDOHUTOMO SEMARANG - Fitri Wiji Astuti; Ekawati Ekawati; Ida Wahyuni (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2017)
Work fatigue is an important issue of hospital management related to human resources. Nurses are vulnerable to fatigue due to some factors such as workload (physical and mental), work shifts, their responsibility, psychological and organizational. This condition can lead to decreased work efficiency, skills and increased anxiety or boredom. Based on preliminary conducted on 14 nurses in 14 wards at psychiatric hospital Dr. Amino Gondohutomo Semarang, showed fatigue symptoms such as exhaustion, stiffness, dizziness, excessive sweating and sleep disorder. The research was aimed to observe the correlation between individual factor, workload, and work shift with work fatigue at nurses in psychiatric hospital Dr. Amino Gondohutomo Semarang. The design was observational analytic with cross sectional approach. The population in this study amounted to 138 nurses, and samples of 58 nurses. Sample was taken with proportionate stratified random sampling. The data was collected by reaction timer, pulse meter and NASA-TLX questionnaire. The chi-square statistical test resulted the related variables are age (ρ-value = 0,019), length of work (ρ-value = 0,006), mental workload (ρ-value = 0,027), and work shift (ρ- value = 0,036). The unrelated variables were gender (ρ-value = 1,000), marital status (ρ-value = 0.200), nutritional status (ρ-value = 0.966), and physical workload (ρ-value = 0.691). The hospital should to organize equal work shift in each ward, provide counseling related to work fatigue, its impact and its prevention.